PREMELTING AND CALCIUM MOBILITY IN GEHLENITE (CA2AL2SIO7) AND PSEUDOWOLLASTONITE (CASIO3) - Bouhifd M.A.; Gruener G.; Mysen B.O.; Richet P. (My University, 2002)
Premelting effects in gehlenite (Ca2Al2SiO7) have been studied by Raman spectroscopy and calorimetry, and in gehlenite and pseudowollastonite (CaSiO3) by electrical conductivity. The enthalpy of premelting of gehlenite is 17.3 kJ mol-1 and represents 9% of the reported enthalpy of fusion, which is in the range of the reported fraction of other minerals. The Raman and electrical conductivity experiments at high temperatures, for gehlenite and pseudowollastonite, show that the premelting effects of both compositions are associated with enhanced dynamics of calcium atoms near the melting point. This conclusion agrees with the results obtained for other minerals like diopside, but contrasts with those found for sodium metasilicate in which the weaker bonding of sodium allows the silicate framework to distort near the melting temperature and deform in such a way to prefigure the silicate entities present in the melt.
Keywords: GEHLENITE; PSEUDOWOLLASTONITE; ELECTRICAL CONDUCTIVITY; CALORIMETRY; RAMAN SPECTROSCOPY